Peran Cross Selling Dalam Meningkatkan Penjualan Produk Unilever Oleh PT. Multi Pilar Indah Jaya di Pulau Nias - Lase, Asri Sartika; Nov Elhan Gea; Yupiter Mendrofa; Otanius Laia (LPPM Universitas HKBP Nommensen, 2024)
This research evaluates the role of cross-selling in increasing Unilever product sales by PT Multi Pilar Indah Jaya on Nias Island. Cross-selling is a method of offering additional products that are related or complementary to the products previously offered. The aim of this research is to assess the extent to which the cross-selling strategy implemented by PT Multi Pilar Indah Jaya has successfully increased the sales volume of Unilever products on Nias Island, both quantitatively and qualitatively, and to identify factors contributing to the success or failure of the strategy. This research explores internal and external factors that may influence the implementation of cross-selling strategies within the context of distribution companies on Nias Island. The research method used is qualitative, with data collection techniques including in-depth interviews, field observations, and documentation. Sales information is gathered from Admin, Sales Supervisors, and the sales team of PT Multi Pilar Indah Jaya. The data is analyzed using methods of Reduction, Data Presentation, and Conclusion Drawing. The results of the research show that PT Multi Pilar Indah Jaya has been able to better understand the characteristics and preferences of its customers, enabling the company to adopt effective policies for achieving a successful cross-selling strategy, with the goal of increasing sales of Unilever products on Nias Island. Keywords: Cross Selling, sales, Unilever, PT Multi Pilar Indah Jaya, Nias Island